Pengaruh Kesadaran Lingkungan, Sikap Konumen dan Harga Terhadap Keputusan Pembelian Produk Ramah Lingkungan Botol Tumbler (Studi Pada Mahasiswa S1 Fakultas Ekonomi Dan Bisnis Universitas Trunojoyo Madura) - Safitri, Dina; Setiyarini, Triana (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of environmental awareness, consumer attitudes and prices towards and prices on purchasing decisions for eco-friendly tumbler bottles. This study used a quantitative approach with data collection methods distributing questionnaires to students of the Faculty of Economics and Business, University of Madura. The sample 97 respondent. Data analysis techniques were performed using descriptive statistical analysis. Based on the results of data analysis and discussion of prices, the t value of the environmental awareness variable with sig. 0.515 where 0.05 does not have a significant influence on the purchasing decisions. The t value of consumer attitude variable with sig. 0.003 where 0.05, consumer attitudes have a significant influence on purchasing decisions. The value of the price variable t value with sig. 0.000 where 0.05, the price has a significant influence on the purchase decision. Simultaneously, Environmental Awareness, Consumer Attitude and Price have a significant effect on Purchase Decision, with an F-count of with a significance value of 0.000 0.05.